2019
DOI: 10.3389/fpsyg.2019.01187
|View full text |Cite
|
Sign up to set email alerts
|

Educational Responses to Students With High Abilities From the Parental Perspective

Abstract: Students who have high abilities demand educational responses, both inside and outside of the classroom. The best type of educational strategy depends on the characteristics of the students, the school, the educational system, and the country. For this reason, the level of attention paid to high-ability students can vary across nations. To guarantee the efficacy of programs that are implemented both inside and outside of school, it is essential to offer to these students the support that they need. The student… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 30 publications
0
12
0
3
Order By: Relevance
“…The main advantage of this software is that the program establishes categories through the analysis it performs (Illia et al, 2012). ALCESTE has been widely used in high capacity studies (Villatte et al, 2011;Rodríguez-Naveiras et al, 2019), the study of COVID-19 representations in children (Idoiaga et al, 2020), and studies on episodic memory and self-awareness in Asperger Syndrome (Chaput et al, 2013), among others.…”
Section: Discussionmentioning
confidence: 99%
“…The main advantage of this software is that the program establishes categories through the analysis it performs (Illia et al, 2012). ALCESTE has been widely used in high capacity studies (Villatte et al, 2011;Rodríguez-Naveiras et al, 2019), the study of COVID-19 representations in children (Idoiaga et al, 2020), and studies on episodic memory and self-awareness in Asperger Syndrome (Chaput et al, 2013), among others.…”
Section: Discussionmentioning
confidence: 99%
“…A wide range of resources are available for offering enrichment to students with high intellectual abilities depending on the characteristics of the educational system, the school, the students, etc. (Rodríguez-Naveiras et al, 2019), including establishing agreements with local actors associated with higher education, for example, participating in university mentorships (Ibáñez et al, 2020) or enrichment programs (Sastre-Riba, 2013). Being able to work in special programs with like-minded peers and experts is a measure valued by gifted students enrolled in mixed schools (Ireland et al, 2020).…”
Section: Enrichment Program At the Catholic University Of Valenciamentioning
confidence: 99%
“…In this regard, gifted students cannot be overlooked (Herranz and Sánchez, 2019). Our laws on education conform to the necessity of adequately addressing pupils' specific characteristics, but in practice, they are not often receiving what they truly need (Ersoy and Uysal, 2018;Parr and Stevens, 2019;Rodríguez-Naveiras et al, 2019), leading to underachievement (Siegle, 2018;Lamanna et al, 2019) and even school failure and early school withdrawal (Blaas, 2014).…”
Section: Introduction Educational Inclusionmentioning
confidence: 99%
“…An essential variable of the family context is the educational level of the parents, which, in turn, is closely associated with variables of the socio-economic and environments, and with what is referred as family cultural capital [60,63]. This relationship depends significantly on factors such as the access to cultural activities and goods at home and the education of parents, parallel to their expectations, their beliefs about education and their involvement (affective and instrumental) in educational guidance to their children [64][65][66][67][68][69]. The studies by Hernández and Bazán [70] have shown the association among parents' education levels, the type of support they give to their children's education, and its effects on their children academic results or school trajectories.…”
Section: Family Cultural Capital School Trajectories and Psychologimentioning
confidence: 99%